MICROCREDIT: A MEANS OF FINANCIAL STABILITY OR A TOOL FOR EXPLOITATION? - S, Shaniba; B, Gopika; N, Sivakumar; S, Nehru (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Microcredit has received a lot of attention lately since it is hailed as a revolutionary financial instrument for reducing poverty and promoting economic empowerment. This piece explores the dual nature of microcredit, examining how it may be used as a tool for potential exploitation as well as a means of achieving financial security. This research highlights the critical role that microcredit has had in giving marginalised populations access to capital by drawing on an extensive analysis of empirical evidence. It looks at how microcredit initiatives have boosted community development, entrepreneurship, and income production, thereby empowering people, especially women. These encouraging results highlight microcredit’s capacity to promote economic resilience and financial stability. On the other hand, the research also reveals the negative aspects of microcredit. The research indicates that low-income individuals with inadequate financial and educational backgrounds are using microcredit to cover everyday household needs because there are insufficient regulating authorities in place. With no other feasible choice, these people are turning to microcredit, where they frequently run into predatory practises such excessive interest rates and forceful loan practises. The positive effects of microcredit are overshadowed by these practises, which give rise to serious ethical and social concerns.